New generation direct oral anticoagulants effects on thrombotic events prevention after atrial fibrillation. - Sultonovna, Ergasheva Yulduz; Esanmurodova, N.; Gulnoza, Rustamova; Diyorbek, Yoqubov; Eshchanova, Nasiba; Ilkhom, Abdurakhmonov; Umarjanovich, Satvaldiyev Ixtiyarjon (Revista Latinoamericana de Hipertensión, 2025)
This study aimed to assess the efficacy of novel direct oral anticoagulants (DOACs) in preventing thrombotic events following atrial fibrillation (AF) within the Uzbek patient demographic. Conducted as a prospective, multicenter cohort study, it involved 500 patients diagnosed with non-valvular AF from 2022 to 2024. Participants were categorized into two groups: one receiving DOACs (apixaban, rivaroxaban, and dabigatran) and a control group treated with warfarin, with follow-up extending over 18 months. The findings revealed that the administration of DOACs led to a notable decrease in the occurrence of thrombotic events, such as ischemic stroke and systemic embolism (hazard ratio [HR]: 0.65; 95% confidence interval: 0.52-0.81; P < 0.001). Furthermore, the incidence of major bleeding was significantly lower in the DOAC group compared to the warfarin group (3.2% versus 7.8%; P = 0.02). Sub-analyses highlighted improved adherence to DOACs, attributed to the absence of the need for regular INR monitoring. This research supports the notion that new-generation anticoagulants, which demonstrate enhanced efficacy and a favorable safety profile, represent an optimal treatment choice for managing AF patients in the Uzbek population.